Social media content strategy for sport clubs to drive fan engagement. (September 2021) - Annamalai, Balamurugan; Yoshida, Masayuki; Varshney, Sanjeev; Pathak, Atul Arun; Venugopal, Pingali
Abstract: Social media brand pages act as excellent means for engaging consumers. While most sport clubs use social media such as Facebook to enhance fan engagement, extant research has given limited attention. This study aims to understand the impact of content type and vividness of Facebook content shared by sport clubs, on fan engagement. The findings are based on a netnography study on the Facebook platform among six cricket clubs of a major league – the Indian Premier League, covering approximately 4000 club-generated posts and recording more than 76 million impressions on the six sport clubs' official fan pages over a span of 3 years (2015–2017). The volume of likes, comments, shares, and the valence of comments, on the Facebook fan pages, are used to measure fan engagement. We found that the social content garnered maximum contribution, while the remuneration-related content resulted in the least contribution. Photos, representing low vividness content, garnered the maximum number of likes and comments, while high vividness content (i.e., videos) were shared most often. Furthermore, the moderating impact of team performance and seasonality on the relationship between content type and fan engagement are explicated. This study contributes to the emerging research on social media in consumer engagement and sport marketing literature and provides practical prescriptions for sport clubs to enhance their ability to engage their fan base online. Graphical abstract: Image 1 Highlights: Contribute to emerging research on the nature of social media engagement by fans. Investigates the effect of sport club shared content on fan engagement. Explicates the moderating impact of team performance and seasonality. Social content received maximum volume and valence measures of fan engagement. Photos, representing low vividness, received maximum Facebook likes and comments.